Multiwavelength studies of classical novae - Aydi, Elias (Department of Astronomy, 2019)
Classical novae are transient astronomical events resulting from an eruption on the surface of an accreting white dwarf in interacting binary stars, namely cataclysmic variables. These eruptions and their progenitors are ideal astronomical events/objects to study a variety of interesting topics, such as mass-transfer mechanisms, binary evolution, and thermonuclear and radiative emission processes. Novae share some general observational characteristics during their eruption phases, yet each nova is new and can show unique light-curve and spectral developments. Therefore, carrying out detailed multiwavelength studies of individual novae is important to provide an holistic picture of the eruption development with the ultimate aim of a general understanding of the physical mechanisms involved in nova eruptions, as well as the structure and evolutionary condition of their progenitors. This dissertation presents detailed multiwavelength studies of three nova events, namely V5852 Sgr, SMCN 2016-10, and V407 Lup, as a series of chapters (papers). Our data were collected using several ground-based and space telescopes including: high- and mediumresolution optical spectroscopy from SALT, SOAR, and FLOYDS, optical and near-infrared photometry from IRSF, OGLE and SMARTS, UV and X-ray data from Swift, Chandra, and XMM-Newton. In the second chapter, we present an optical and infrared study of the unusual nova V5852 Sgr. This nova is a moderately fast nova showing features of the Fe II spectroscopic type. The light-curve development is unique, showing a combination of several light-curve classes. Estimates of the distance and measurements of the line velocities suggest that the nova might be associated with the Sagittarius stream. If so, it would be the first nova to be discovered in a dwarf spheroidal galaxy. The third chapter presents a multiwavelength study of the very fast nova SMCN 2016-10a. The fast light-curve development suggests that the system hosts a massive white dwarf (& 1.25 M), in good agreement with the high temperature of the super-soft X-ray emission and the turn-on/turn-off time of the super-soft state. At the distance of the Small Magellanic Cloud our measurements suggest that SMCN 2016-10a is the brightest nova in the Small Magellanic Cloud and one of the brightest novae on record, with an absolute maximum magnitude of ∼ −10.5 in the V -band. Chapter four is a multiwavelength study of nova V407 Lup. With a light-curve decline time t2 ≤ 2.9 d, this is one of the fastest known examples and the white dwarf is possibly more massive than 1.25 M. Our set of optical, UV, and X-ray data suggest that this system is an intermediate-polar cataclysmic variable based essentially on the presence of two periodicities (3.57 h and 565 s) in the light-curves. These periodicities are attributed to the orbital period of the binary and rotational period of the white dwarf. The late optical spectra (taken from day 165 post-eruption) show narrow and moving lines of He II and O VI, possibly associated with accretion regions within the binary system. This, along with the X-ray light-curves and spectra, suggest that the accretion probably resumed around 168 days post-eruption. These studies are modest, yet essential steps in the quest for a better understanding of nova eruptions. They also demonstrate the importance of multiwavelength follow-up of novae for constraining the physical parameters of the eruption, the ejecta, and the properties of the progenitor. In the era of large all-sky surveys, such as the All-Sky Automated Survey for Supernovae and eventually the Large Synoptic Survey Telescope which have been and are ex- pected to find a large number of optical transients and classical novae, similar multiwavelength follow-up will play a crucial role for initially identifying these transient events and further understanding their physical behaviour.